PENGARUH STRESS KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Santi, Santi (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
This study aims to determine the effect of work stress, work environment, work engagement, job satisfaction on shrimp pond employees in the Pidie Sigli Aceh area. The main problem in this research is job satisfaction. This research is a quantitative research with a survey method of respondents. The population in this study were employees who worked in several shrimp ponds in the Pidie Sigli Aceh area, totaling 89 employees. Data collection techniques in this study used a list of questions or questionnaires. The data analysis tool used in this study is SmartPLS. Based on the results obtained, the factors that influence job satisfaction are the work environment and work engagement. This is evidenced by the results of hypothesis testing which shows a t-count value of 3.673 ≥1.96 with a p-value of 0.000 ≤ 0.05 and t-count of 4.420 with a p-value of 0.000 ≤ 0.05, while job stress has no effect on job satisfaction Shrimp pond employees in the Pidie Sigli Aceh area.